Isolation and characterization of apoptosis-inducing compounds from Clinacanthus nutans - Hazrulrizawati, Abd Hamid (2014)
Clinacanthus nutans have been used in traditional herbal medicine for cancer prevention but specific bioactive compounds responsible for the observed activities have not been explored. Different solvents such as methanol, chloroform, ethyl acetate and hexane were used for the extraction. The extracts were subjected to in vitro antioxidant and anticancer activities. Phytochemical screening was done by determining total phenolic content (TPC) and total flavonoid content (TFC). The methanol extract of C. nutans showed significant antioxidant activity for 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity (IC50 127.09± 0.042 μg/mL), total reduction capability (IC50 469.13 ± 0.05 μg/mL and anticancer activity on HT29 (IC50 36.19 ± 1.06 mg/mL), HepG2 (IC50 48.37 ± 0.026 mg/mL) and MCF-7 (IC50 54.16 ± 0.99 mg/mL) after 72 h of treatment. Total phenolic content (TPC) was found to be highest in chloroform, which was 119.29 mg of gallic acid equivalent (GAE) a nd total flavonoid content (TFC), methanol was performed the highest value, which is 937.67 mg of butylated hydroxytoluene (BHT). Purification of MeOH extracts afforded two new sulphur-containing compounds, named clinamide D and E (1-2). Compound (1) proved to be more active with IC50 value for DPPH radical scavenging of 118.27± 0.01μg/mL and reduction of Fe3+–TPTZ complex of 386.24 ± 0.02, higher than that standard ascorbic acid. Sulphur-containing compounds isolated from. C. nutans is a potential source as a natural antioxidant.